SOIL CORROSIVITY AND OVERBURDEN PROTECTIVE CAPACITY OVER AQUIFER SYSTEM IN KWAL KANKE NORTHENTRAL NIGERIA - JOSEPH. A., BULUS; SHEDRACK. D., BRAINET (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2021)
A geophysical survey was carried out in Kwal, Kanke Local Government Area of Plateau State, northcentral Nigeria using electrical resistivity soundings method. This study aimed to demarcate zones that are very susceptible to groundwater contamination from surfacepollutants and subsurface soils that are corrosive to utility pipes. Schlumberger configurations were used to delineate the subsurface geologic layers, corrosivity level and aquifer protective capacity. Fourty (40) Vertical Electrical Sounding (VES) data were acquired using ABEM Terrameter SAS 300B and ABEM 2000 booster resistivity meter with half-current electrode separation (AB/2) of 1 to 125 m. The interpretations of the data collected were aided by computer assisted iterative using the computer iteration algorithm WINRESIST Version 1.0, MS Excel 2016 and surfer 11 software. The curve types obtained include: A, Q, H, K, AK, HA, QH, AA, KH and HK types. Four (4) distinct geoelectric layers were identified namely: topsoil, clayey layer, fractured basement and fresh basement. The topsoil is composed of moderately corrosive materials depicted with green colour having resistivity values in the range of 10 to 60 Ωm with frequency distribution of 22.50%. Slightly corrosive materials with resistivity values of 60 < ρ < 180 Ωm and frequency distribution of 57.50% is symbolized with yellow colour while the practically non-corrosive with resistivity values in excess of 180 Ωm have 20.00% frequency distribution represented with pink colour. The second layer is made up of moderately corrosive materials having resistivity values in the range of 10 to 60 Ωm (green colour) with frequency distribution of 30.00%. Slightly corrosive materials having resistivity values of 60 to 180 Ωm have frequency distributions of 20.00% is denoted with yellow colour. The practically non-corrosive portions have resistivity values above 180 Ωm and frequency distribution values of 50.00% are depicted with pink colour. Zones of moderate (pink colour), weak (green colour) and poor (yellow colour) overburden protective capacity were delineated, with longitudinal conductance (S) values of 0.2 < S < 0.69, 0.1 < S < 0.19 and S < 0.1 mhos, respectively. On a regional consideration, 25.00%, 52.50% and 22.50% of the study area is characterised by overburden materials of poor, weak and moderate protective capacity respectively. The measured overburden thickness ranges from 2.6 to 29.6 m. Zones of moderate protective capacity have thick aquifer with thick clay materials above the aquifer that act as seal while areas with poor to weak protective capacity are susceptible to infiltrating contaminating fluid.